Fractional Order Riemann Zeta Factorial Function: A Recent Study - G. Britto Antony Xavier; T. Sathinathan; D. Arun (Theory and Practice of Mathematics and Computer Science Vol. 10, 2021)
The purpose of this article is to apply zeta factorial function theory to fractional order Riemann zeta ?factorial function. Several formulae on the fractional order Riemann zeta factorial function can be obtained using the inverse principle of the generalised difference operator. Findings are numerically validated using appropriate examples.